Risk Factors Associated With Worse Clinical Outcomes of Ankle Fractures Involving the Posterior Malleolus. Issue 1 (February 2023) - Rajan, Lavan; Eble, Stephanie; Kim, Jaeyoung; Kukadia, Saanchi; Kumar, Prashanth; Day, Jonathan; Cho, David; Drakos, Mark; Ellis, Scott
Background: Ankle fractures involving the posterior malleolus (PM) tend to result in inferior clinical outcomes compared to other ankle fractures. However, it is unclear which specific risk factors and fracture characteristics are associated with negative outcomes in these fractures. The aim of this study was to identify risk factors for poor postoperative patient-reported outcomes in patients with fractures involving the PM. Methods: This retrospective cohort study included patients who sustained ankle fractures involving the PM between March 2016 and July 2020 and had preoperative computed tomography (CT) scans. In total, 122 patients were included for analysis. One patient (0.8%) had an isolated PM fracture, 19 (15.6%) had bimalleolar ankle fractures involving the PM, and 102 (83.6%) had trimalleolar fractures. Fracture characteristics including the Lauge-Hansen (LH) and Haraguchi classifications and posterior malleolar fragment size were collected from preoperative CT scans. Patient Reported Outcome Measurement Information System (PROMIS) scores were collected preoperatively and at a minimum of 1 year postoperatively. The association between various demographic and fracture characteristics with postoperative PROMIS scores was assessed. Results: Involvement of more malleoli was associated with worse PROMIS Physical Function ( P  = .04), Global Physical Health ( P  = .04), and Global Mental Health ( P  < .001), and Depression scores ( P  = .001). Elevated BMI was also associated with worse PROMIS Physical Function ( P  = .0025), Pain Interference ( P  = .0013), and Global Physical Health ( P  = .012) scores. Time to surgery, fragment size, Haraguchi classification, and LH classification were not associated with PROMIS scores. Conclusion: In this cohort, we found that trimalleolar ankle fractures were associated with inferior PROMIS outcomes compared with bimalleolar ankle fractures involving the PM in multiple domains. Level of Evidence: Level III, retrospective cohort study.